WAGE BILL AND FINANCIAL PERFORMANCE OF LEVEL 5 FAITH BASED HOSPITALS IN NAIROBI METROPOLITAN, KENYA - Kisio, Benedict; Githui, Thomas; Omurwa, John (International Journal of Finance and Accounting, 2021)
Purpose: The main objective of this study was to examine the effect of wage bills on financial performance of Level 5 faith based hospitals in Nairobi Metropolitan, Kenya. Materials and Methods: A descriptive survey was used in this study. The target population comprised of 6 Level 5 faith based hospitals, 30 staff members in Finance departments and 6 HR Managers. In total, the target population was 36. Census technique was used to select all the 36 respondents to participate in the study. Questionnaires were used to collect the data from the respondents whereas the financial statements were also obtained from the hospitals. Cross sectional technique was used to obtain data from the financial statements of the 6 Level 5 Faith Based Hospitals. Quantitative approach of analysis was used in the study whereby descriptive and inferential statistics were involved. The data was analyzed with the use of SPSS and summarized in frequencies and percentages. The summarized data was presented using figures and tables. Results: The findings showed that salaries affected the financial performance of the faith based hospitals to some extent. Provision of performance related incentives and allowances affect the financial performance of the faith based hospitals to a greater extent. Majority of the respondents were positive that wage policy has an effect on the financial performance of faith based hospitals. Basic salary (Beta=.298) and wage policy (Beta=.364) were found to be positively related to the financial performance of faith based hospitals. On the other hand, performance related incentives and allowances had a negative inverse association. It was also found that majority of the hospitals are providing a wage bill between 36-40%. This is fairly good because it is close to the internationally accepted wage bill percentage standard of 35%. Unique contribution to theory, practice and policy: The study recommended that the faith based Hospitals should work towards improving the quality of services offered in their Hospitals so as to help raise more revenue that can support the operations of the Hospital. It is also recommended that the Hospital should avoid giving unnecessary incentives to the employees. Instead, it should work towards coming up with a structure in which incentives are provided based on employees performance and their input to the organization. The Hospitals should also conduct wage surveys and benchmarking activities with other related organizations. Through these surveys and activities the Hospitals will be able to monitor the average wage increase in other Hospitals and Juridictions. The study finally recommends Hospital wage bills should not exceed 40% of the total Revenue because it may lead to delayed payment of salaries or compromising some expenditures due to financial pressure.